أدب الطفل مفهومه وخصائصه وفنونه في ليبيا محمد المسلاتي( ليل الجدَّات ) أنموذجاً (Comprehensive Journal of Science, 2025)
group within societ examinesa this study And explores its role in contributing to educational religious pedagogical and social development the study is based 0n the principle that lslam has given exceptionel attention to ch ildhood recognizing its deep impact on shaping an individuals character childrens literature is closely linked tool for guiding this group toward paths that strengthen their intellectual emotional and social growth through this perspectve the stud y aims to highlight the importance in order to support the proper development of the younger generation .
Keywords: childrensliterature.its importance.themes. Characterists ,goals of childrens literature ,artistic study Of literary forms